Von Ein- und Ausschlüssen in Europa Eine ethnographische Studie zu EU-Migration und Wohnungslosigkeit in Deutschland - Haj Ahmad, Marie-Therese (2022)
In her ethnographic study, Marie-Therese Haj Ahmad turns to the interface of intra-European migration and homelessness. The focus is on questions of transnational social rights as well as social work practice in this field of action. The readers accompany a fictitious character to various places that are relevant for homeless EU citizens: a social welfare office, a doctor's practice for homeless people and a day centre for homeless people. There they witness the negotiations and struggles for (social) rights, recognition and social justice. In them, the violent history of Europe appears, which continues to this day in intra-European differentiations and exclusions. Racism, anti-Slavism and classism characterise the everyday life of homeless EU citizens. At the same time, it becomes clear that although social work is part of the inner-European border regime, it can also have a resistant effect within it. Finally, the study shows how the practice of intra-European migration challenges the narrative of a homogenous EU-Europe as a place of equality and human rights.